PENCURIAN IDENTITAS KATEGORI & KASUS - Rifqi Mahmud (Cyber Security dan Forensik Digital, 2019)
Identity is a characteristic or sign that is unique and inherent in an individual and has its own valuable value in the form of information contained in it. The importance of the information contained in one's identity makes identity theft something to be wary of where losses can be in the form of finance, property, reputation and even emotional loss can also be caused by theft of identity theft. Some categories of identity theft that often occur are criminal identity theft, theft identity, identity cloning, medical identity theft, child identity theft.